Solar Charging Station for Easy Bikes in Bangladesh: Validation and Post-Model Evaluation (GUB Journal of Science and Engineering, 2024)
The significance of renewable sources of energy is enormous in reducing the demand, use, and also price of fossil fuels following recent advances in related technologies allowing for the development of solar-powered cars. The number of users of electric vehicles (EVs) is increasing rapidly day by day all over the world. Due to the growing number of users of EVs, our existing electrical network is facing a lack of electric power because of the overload. As the number of electric and hybrid vehicles increases, efficient and integrated charging stations must be developed to solve the overload issues in existing networks. To address this, the paper proposes using onsite renewable energy sources such as solar energy and existing networks to improve the efficiency and effectiveness of charging stations. Combining photovoltaic with battery storage in a grid-connected system ensures the reliable functioning of the hybrid charging station. The paper focuses on the post-model evaluation, charging station distribution and location, business model, limitations, and software simulation and corresponding calculation. The results show that hybrid-powered charging stations can be economical, dependable, and efficient enough to fulfill the various demands of electric vehicle loads.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 10(1), 2023 P 1-9